Explosions in November: the first 33 years of Huddeersfield Contemporary Music Festival - Steinitz, Richard (Huddersfield University of Huddersfield Press, 2011)
Explosions in November tells the story of one of Europe's leading cultural institutions, Huddersfield Contemporary Music Festival (hcmf), through the eyes of its founder and former artistic director, Professor Richard Steinitz. From its modest beginnings in 1978, when winter fog nearly sabotaged the inaugural programme, to today's internationally renowned event, hcmf has been a pioneering champion of the best in contemporary music. Now Richard Steinitz brings his insider view on the people behind the festival and how they made each year a success. He recalls his encounters with some true giants of music, including Boulez, Berio, Cage, Ligeti, Stockhausen and Xenakis. Discover how the author survived mushroom-hunting with John Cage, how the festival engineered a historic reconciliation between Cage and Pierre Boulez and how a ceiling fitting nearly brought Stockhausen's career to a premature end. It is a compelling, inspiring and often entertaining story. Explosions in November reveals the full picture of a festival that continues to surprise, delight and provoke its audiences to this day.